Analisis Efisiensi Industri Perbankan: Aplikasi Metode Data Envelopment Analysis (DEA) - , Evi Feronika, Dr. Khomsiyah, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Objective of this research is to examine the efficiency at Indonesia banking industry efficiency. The research was conducted at Indonesia banking industry with number of sample for 30 banks from 120 bank at Indonesia. In order to examine the efficiency banking industry, we used Data Envelopment Analysis Method (DEA) dan Stochastic Frontier Approach (SFA) Results are: (1) There is unefficiency of Indonesia banking industry at 2006 â 2010, this result from efficiency average for 5 year period of time show under 100 %. (2) There is 3 bank which efficiecy for 2006 â 2010, it is Panin Bank, Standard Chartered Bank, and Victoria Bank. (3) Most factor make unefficiency at Indonesia banking industry are salaries/ allowances, interest expense, and deposits from customers (input variable). (4) Result of SFA and DEA show thatâs Indonesia bank is unefficiency. Value efficiency of SFA is 99,53 % and DEA is 86,90%. Whereas suggestions to be conducted are : (1) The unefficient banking, able evaluation for internal policy to get more efficient. (2) For upgrade capacity and marketing scope for efficient banking, needed government and monetery regulator policy for support thatâs.